Effects of Different Weak Small Organic Acids on Clofazimine Solubility in Aqueous Media - Igor A. Topalović; Olivera S. Marković; Miloš P. Pešić; Mufaddal H. Kathawala; Martin Kuentz; Alex Avdeef; Abu T. M. Serajuddin; Tatjana Ž. Verbić (Pharmaceutics, 2024)
Background/Objectives: Clofazimine (CFZ) is a Biopharmaceutics Classification System (BCS) II drug introduced in the US market in 1986 for the treatment of leprosy. However, CFZ was later withdrawn from the market due to its extremely low aqueous solubility and low absorption. In the literature, the intrinsic solubility of CFZ has been estimated to be <0.01 μg/mL, and solubilities of its different salt forms in simulated gastric and intestinal fluids are <10 µg/mL. These are extremely low solubilities for the dissolution of a drug administered orally at 100–200 mg doses. Methods: In the present investigation, seven weak organic acids (adipic, citric, glutaric, maleic, malic, succinic, and tartaric) were tested by determining the aqueous solubility of CFZ as the function of acid concentration to investigate whether any of the acids would lead to the supersolubilization of CFZ. Results: There were only minimal increases in solubilities when concentrations of acids in water were increased up to 2.4 M. The solubilities, however, increased to 0.32, 1.23, and 10.68 mg/mL, respectively, in 5 M solutions of tartaric, malic, and glutaric acids after equilibration for 24 h at 25 °C. Crystalline solids were formed after the equilibration of CFZ with all acids. Apparently, salts or cocrystals were formed with all acids, except for glutaric acid, as their melting endotherms in DSC scans were in the range of 207.6 to 248.5 °C, which were close to that of CFZ itself (224.8 °C). In contrast, the adduct formed with glutaric acid melted at the low temperature of 77 °C, and no other peak was observed at a higher temperature, indicating that the material converted to an amorphous state. Conclusions: The increase in CFZ solubility to >10 mg/mL in the presence of 5 M glutaric acid could be called supersolubilization when compared to the intrinsic solubility of the basic drug. Such an increase in CFZ solubility and the conversion of the glutarate adduct to an amorphous state are being exploited to develop rapidly dissolving dosage forms.